Menelisik Pemikiran Asghar Ali Engineer dan Upaya Rekonstruksi Pemikiran Islam - Imam Herdian (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2025)
This article examines Asghar Ali Engineer's ideas about Islamic Thought. Engineer criticizes the discourse of Islamic thought that has developed to date more often placing religion as something absolute and placing it as something sacred, untouchable for various reasons, and the way of understanding it is doctrinaire, so that it seems rigid and does not create space for the human critical realm. This research uses qualitative research by collecting data and information from various manuscripts, books and journals. The main aim of this article is to show the urgency of reconstructing Islamic thought. These findings show that efforts to reconstruct Islamic thought are a necessity if we restore the Islamic elan vitas inherited by the prophet Muhammad to create justice and mercy for all of nature. There are at least four attempts to reconstruct Islamic thought from several socio-religious issues which according to the author are the main focus in his mission of renewal. It can be seen that Engineer wants to emphasize that religion not only functions as a belief system, but also as a tool for creating positive social change.